Originally Posted by
celtic1234 Hi all
I am trying to solve the following problem and my answer does not match up with that in the book.I have done it 4 times and have got it wrong each time.
Can somebody do it before it drives me mad.
Find dy/dx as a function of x and y for y=x-y+2y^3-3Lnx
differentiate both sides;
dy/dx= 1-(dy/dx)+6y^2.(dy/dx)-3x^-1
2dy/dx-6y^2.(dy/dx)=1-3x^-1
dy/dx(2-6y^2)=1-3x^-1
dy/dx=(1-3x^-1)/ (2-6y^2)
The answer in my book is dy/dx=(x-3)/[3x(1+2y^2)]
I have followed the examples in the book fine, -this one is driving me mad.
Help appreciated
John